Analysis of deoxyribonucleic acid replication in human X chromosomes by fluorescence microscopy. - Willard, H F (1976)
The genetically inactive, late-replicating human female X chromosome can be effectively distinguished from its more active, earlier-replicating homologue, when cells are grown according to the appropriate BrdU-33258 Hoechst protocol. Results obtained from a fluorescence analysis of DNA replication in X chromosomes are consistent with those from previous autoradiographic studies, but reflect additional sensitivity and resolution offered by the BrdU-Hoechst methodology. Both qualitative and quantitative differences in 33258 Hoechst fluorescence intensity, reflecting alterations in replication kinetics, can be detected between the two X chromosomes in female cells. The pattern of replication in the single X chromosome in male cells is indistinguishable from that of the early female X. Intercellular fluctuations in the distribution of regions replicating early or late in S phase, particularly with reference to the late female X, can be localized to structural bands, suggesting multifocal control of DNA synthesis in X chromosomes.